Economic Feasibility of a Small-Scale Wind Turbine in Coastal Area of South Sulawesi. Issue 1 (November 2021) - Mahmuddin, F; Puspitasari, N; Pawara, M U
Abstract: To evaluate the exploitation potential of wind energy in the coastal area of South Sulawesi, Indonesia, an investigation on the economic feasibility of this project was performed. A 300-watt horizontal wind turbine was used as an example installed turbine. The wind speed range of 4-7 m/s which was the wind speed data in the coastal area of South Sulawesi was computed. The main economic analysis method employed was Capital Budgeting Analysis (CBA) method. In this method, 4 (four) indicators were used to evaluate the feasibility of the project which are payback period (PBP), net present value (NPV), internal rate of return (IRR), and benefit-cost ratio (BCR). A visual basic computer program based on the CBA method was also developed to make the computation more convenient. From the study, it was found that the wind speed range of 4-6 m/s resulted in a non-feasibility project while the highest wind speed (7 m/s) was found to be quite strong to make the project feasible.